1998
DOI: 10.1002/(sici)1097-4547(19981001)54:1<1::aid-jnr1>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase and inflammation in Alzheimer's disease: Experimental approaches and clinical interventions

Abstract: Many epidemiological studies suggest that use of non-steroidal anti-inflammatory drugs (NSAIDs) delay or slow the clinical expression of Alzheimer's disease (AD). While it has been demonstrated that neurodegeneration in AD is accompanied by specific inflammatory mechanisms, including activation of the complement cascade and the accumulation and activation of microglia, the mechanism by which NSAIDs might affect these or other pathophysiological processes relevant to AD has been unclear. New evidence that cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(21 citation statements)
references
References 48 publications
0
18
0
3
Order By: Relevance
“…COX-2 participates in activity-dependent synapse formation, remodeling and post-synaptic signaling [7,19]. In addition, COX-2 is involved in mechanisms of neuronal death and survival [20].…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 participates in activity-dependent synapse formation, remodeling and post-synaptic signaling [7,19]. In addition, COX-2 is involved in mechanisms of neuronal death and survival [20].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclooxygenase (COX) converts membranederived arachidonic acid to prostaglandins, and generates free radicals: COX-2 is of primary importance in the inflammatory response (Pasinetti 1998;Lee et al 2008). It has been reported that systemic LPS treatment reduces brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) levels in the hippocampus (Guan and Fang 2006;Schnydrig et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…COX-1 is expressed constitutively in many cell types, whereas COX-2 expression is generally induced by cytokines and other stress-induced stimuli [21]. In brain, COX-2 is present in selected neurons and its expression is upregulated in numerous pathological conditions, including Alzheimer's disease [22]. In addition, consistent with the inflammation hypothesis, epidemiological analysis has indicated that nonsteroid anti-inflammatory drugs (NSAIDs) may prevent or delay the progress of PD.…”
Section: Discussionmentioning
confidence: 96%
“…These NSAIDs are believed to target cyclooxygenase (COX), of which there are two isoforms, COX-1 and COX-2 [23]. Therefore, it is now believed that COX-2 is of primary importance in the inflammatory response [3,8,11,22,24]. JNKs (c-Jun N-terminal kinases) are a subfamily of mitogen-activated protein kinases.…”
Section: Discussionmentioning
confidence: 99%